Sex-Specific Differences in the Associations Between Omega-6 Polyunsaturated Fatty Acids and Type 2 Diabetes in Chinese People - Li, Yingying; Shen, Hui; Li, Yike; Bi, Mei; Bi, Yanhong; Che, Xiaoyu; Tian, Simiao; Liu, Yazhuo (Frontiers in Nutrition, 2021)
Background: Some evidence indicates a potential beneficial effect of omega-6 polyunsaturated fatty acids (n-6 PUFAs) on type 2 diabetes mellitus (T2DM); however, the findings to date remains inconclusive and little is known about whether sex modifies these associations. Therefore, this study aimed to investigate potential sex-specific differences in this associations among Chinese adults. Methods: We conducted a cross-sectional study in an area of Dalian city, China; Chinese men and women who attended the Department of Clinical Nutrition and Metabolism between January and December 2020 were invited to participate in this study. All participants were assessed for basic demographic characteristics, fasting blood glucose, HbA1c, and other serum biomarkers and serum phospholipid FAs. Results: In total, 575 Chinese adult participants (270 men and 305 women) were included in the analysis. Hypertension and dyslipidaemia were more common among men than women, but there were no significant differences between the sexes in fatty acid composition, except for eicosadienoic acid (EA; 20:2n-6) and total monounsaturated fatty acids (MUFA). The age-adjusted OR for having T2DM in the highest quartile of arachidonic acid (20:4n-6) level was 0.47 (95% CI, 0.22, 0.98) in men, and this association remained consistently significant in the fully adjusted multivariate models. In contrast, no significant associations between n-6 PUFAs and T2DM risk were observed in women, regardless of model adjustment. Conclusions: In conclusion, these results demonstrate a notable sex-specific differences in the associations between n-6 PUFAs and T2DM. Higher n-6 PUFA status may be protective against the risk of T2DM in men.